Removal of quinclorac herbicide from aqueous solution by chitosan/montmorillonite bionanocomposite. Issue 52 (7th November 2016) - Ding, Chunxia; Gong, Daoxin; Yu, Peng; Shao, Jihai; Zhong, Mei-E
Abstract: Chitosan–montmorillonite bionanocomposite (CTS–MMT) was prepared for removing the herbicide quinclorac (QC) from aqueous solution. The resulting nanocomposites were characterized by X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET) surface area and Barrett–Joyner–Halenda (BJH) pore size distribution analysis. The adsorption of QC onto CTS–MMT as a function of adsorbent dosage, pH, temperature, ionic strength, contact time, and initial QC concentration was investigated by conducting batch adsorption experiments. The results showed that CTS–MMT exhibited higher adsorption affinity and higher adsorption capacity towards QC than the unmodified montmorillonite. The adsorption kinetics data of QC onto CTS–MMT were well described by the pseudo-second-order kinetics model. Adsorption isotherms fitted well with the Freundlich isotherm model in the heterogeneous adsorption process. Adsorption thermodynamics study indicated that the adsorption of QC onto CTS–MMT was a spontaneous and endothermic process. The QC molecules on CTS–MMT could hardly be desorbed by water, but could be desorbed by 0.1 mol/L NaOH solution. QC adsorption on CTS–MMT may involve electrostatic attraction, cation–dipole, hydrogen bonding, and van der Waals interactions. The findings of this study suggest that CTS–MMT is a potential adsorbent for quinclorac pollution remediation.